Formulation and evaluation of mango butter lipstick / Nur Iffah Iwani Ghazali - Ghazali, Nur Iffah Iwani (2015)
Women have been applying lipstick for ages and the lipstick usage among women has kept increasing in demand. Lipstick is used to enhance the beauty of women's lips. Lipstick formulations are made up of waxes, oils and pigment. The proportion and type of ingredient used in the formulation can affect the lipstick quality. The main aim of this study is to formulate and evaluate mango butter lipstick. Mango (Mangifera indica) is one of the major tropical crop. The food industry will use its flesh and discard tonnes of its peel and seed. Mango butter can be obtained from the kernel of the fruit itself. The incorporated Mango butter is into the lipstick formulations is to give hardness properties of the lipstick. The advantages of mango butter are rich with various vitamins such as vitamin A and C, can act as emollient layer and can protect skin from UV damage.